Preparation method and application of AEM water electrolysis cathode

By preparing the cathode catalyst slurry in AEM electrolytic water and applying anion exchange resin coating, the problems of high overpotential, short life, and easy catalyst fall off in the hydrogen evolution reaction in AEM electrolytic water are solved, and a high activity and high stability AEM water electrolytic cathode is achieved, reducing the energy consumption of electrolytic water.

CN119800403APending Publication Date: 2025-04-11SHANGHAI BRIGHT-H TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510207710.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The hydrogen evolution reaction in AEM electrolytic water faces problems such as high overpotential, short life, and easy catalyst fall off, which restricts the large-scale industrial application of AEM electrolytic water.

Method used

By mixing the cathode catalyst powder, anion exchange resin solution and dispersing agent, uniformly dispersing it, a cathode catalyst slurry is formed, and after applying the surface of the gas diffusion layer, an additional layer of anion exchange resin coating is applied, and the organic solvent is fused to form an interconnected crosslinking channel.

Benefits of technology

Effectively improve the transmission efficiency of OH-ions, reduce the problem of falling off of electrode materials under high electrical density conditions of activation and electrolytic hydrogen analysis, significantly improve the catalytic activity and stability of the cathodic catalytic layer, reduce the ohmic impedance, and accelerate the kinetic process of the electrocatalytic reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800403A_ABST
    Figure CN119800403A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of an AEM water electrolysis cathode, and the preparation method of the AEM water electrolysis cathode comprises the following steps: 1, mixing cathode catalyst powder, an anion exchange resin solution and a dispersant, and uniformly dispersing to form cathode catalyst slurry, the preparation method has the beneficial effects that the anion exchange resin coating is additionally coated, and the anion exchange resin coating and the organic solvent are mutually fused to form a mutually connected crosslinking channel, so that the transmission efficiency of OH <-> ions can be effectively improved, and the problem that an electrode material falls off under the conditions of activation and high current density of hydrogen evolution by electrolysis of water is solved to the greatest extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparing a cathode for electrolyzing water, and in particular to a preparation method and application of an AEM water electrolyzing cathode. Background Art

[0002] The use of renewable energy sources, such as wind energy, solar energy, and ocean energy, for off-grid water electrolysis to produce hydrogen and store energy can effectively improve energy conversion efficiency and contribute to the country's energy "dual carbon" goals. However, in the electrochemical reaction of water electrolysis to produce hydrogen, the slow kinetic process often causes the electrolysis voltage to be higher than the theoretical value. Therefore, how to prepare highly active catalysts to reduce the energy consumption of water electrolysis needs to be solved urgently. At present, the hydrogen evolution reaction (HER) in anion exchange membrane (AEM) water electrolysis faces problems such as high overpotential, short life, and easy catalyst shedding, which restricts the large-scale industrial application of AEM water electrolysis. It is urgent to develop cathode catalysts with excellent performance and stability to accelerate the kinetic process of the electrode and reduce the overpotential of water electrolysis.

[0003] Current solutions and drawbacks:

[0004] 1. Using the CCM method, the cathode catalyst slurry is directly coated on the AEM membrane, so that the catalyst layer is in direct contact with the membrane, which can effectively reduce resistance and improve catalyst utilization. However, the process of this process is relatively complicated. On the one hand, the AEM membrane needs to maintain good anti-swelling properties during the coating process. Once the membrane swells, the catalyst layer will fall off the AEM membrane, causing the catalyst to lose activity. On the other hand, the catalyst layer and the AEM membrane are only bonded by an anionic binder. When the catalytic reaction reaches a high electrical density, stratification will occur between the catalyst layer and the AEM membrane, thereby increasing resistance and affecting OH- ion conduction.

[0005] 2. Integrated self-supporting electrode: through a simple synthesis method, the cathode electrode is synthesized on any porous transport layer. The combination of the cathode catalyst and the porous transport layer can provide more catalytic active sites. However, under high electrical density conditions, this process will cause gas to accumulate in micropores, hindering the occurrence of catalytic reactions, and the transmission distance between the internal local active sites and the AEM membrane is too long, resulting in low ion transmission efficiency, thereby increasing the overvoltage and attenuation life of hydrogen evolution in water electrolysis. Summary of the invention

[0006] In order to overcome the above problems existing in the prior art, the present invention provides a method for preparing and using an AEM water electrolysis cathode.

[0007] In one aspect, the present invention discloses a method for preparing an AEM water electrolysis cathode, comprising the following steps:

[0008] Step 1: Mix cathode catalyst powder, anion exchange resin solution and dispersant and disperse them evenly to form cathode catalyst slurry.

[0009] Step 2: coating the cathode catalyst slurry described in step 1 on the surface of the gas diffusion layer, and obtaining the cathode gas diffusion layer after drying.

[0010] Step 3: coating the surface of the cathode gas diffusion layer in step 2 with an anion exchange resin solution to obtain an anion exchange resin coating.

[0011] Step 4: Soak the cathode gas diffusion layer having an anion exchange membrane resin coating on the surface in step 3 in an organic solvent, and use deionized water to rinse the excess organic solvent on the surface to obtain the highly active and highly stable AEM water electrolysis cathode.

[0012] On this basis, the total mass ratio of the cathode catalyst, the anion exchange resin solution and the dispersant in step 1 is 1:1.1-10.8:4.5-20.

[0013] On this basis, the dispersant includes a mixture of one or more of deionized water, isopropanol, ethanol and ethylene glycol.

[0014] On this basis, the mixed solution is uniformly mixed by one or more of stirring, cell crushing and ice-water bath ultrasonic dispersion.

[0015] On this basis, the coating method includes one or more of coating, transfer and ultrasonic spraying.

[0016] On this basis, the anion exchange resin solution is coated on the surface of the cathode catalyst layer to form an anion exchange resin coating with a coating thickness of 5 to 20 um.

[0017] On this basis, the organic solvent includes one or more of ethanol, isopropanol, acetone and dimethyl sulfoxide.

[0018] On this basis, the volume ratio of the organic solvent to deionized water is 1:1-25.

[0019] On this basis, the organic solvent immersion time is 10 to 180 seconds.

[0020] Another aspect of the present invention provides the use of an AEM water electrolysis cathode in an anion exchange membrane electrolyzer for water electrolysis hydrogen separation reaction.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention can effectively improve the transmission efficiency of OH- ions by coating an additional layer of anion exchange resin coating and fusing with the organic solvent to form interconnected cross-linked channels, thereby minimizing the problem of electrode material shedding under high-density conditions of activation and electrolysis of water for hydrogen evolution; at the same time, it can prevent the anion exchange resin solution originally present in the catalyst slurry from agglomerating under drying conditions, thereby significantly improving the catalytic activity and stability of the cathode catalyst layer;

[0023] (2) The AEM water electrolysis cathode prepared by the present invention, on the one hand, under the action of organic solvents, excessive anion exchange resin coating will be dissolved, which can make the polymer main chain structure in the anion exchange membrane stretch during the electrochemical reaction, forming more three-phase interfaces to promote the catalytic reaction; on the other hand, the formed interconnected cross-linked channels can be embedded in the anion exchange membrane during the electrolytic cell assembly process, improving the problem of high resistance between the catalyst layer and the anion exchange membrane due to poor contact;

[0024] (3) The AEM water electrolysis cathode prepared by the present invention can construct a transmission channel that is conducive to ions, electrons, alkali solution, and gas during the anion exchange membrane water electrolysis cell test process, reduce the ohmic impedance, and thus accelerate the electrocatalytic reaction kinetics process. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a performance diagram of the electrolytic cell of Example 1 of the present invention,

[0026] Figure 2 This is a performance diagram of the electrolytic cell of Example 1 of the present invention,

[0027] Figure 3 This is the performance diagram of the electrolytic cell in Example 3 of the present invention,

[0028] Figure 4 This is a performance diagram of the electrolytic cell of Example 4 of the present invention,

[0029] Figure 5 This is a performance diagram of the electrolytic cell of Example 5 of the present invention,

[0030] Figure 6 This is the performance diagram of the electrolytic cell of Comparative Example 1 of the present invention,

[0031] Figure 7 It is the performance diagram of the electrolytic cell of comparative example 2 of the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The present invention discloses a method for preparing an AEM water electrolysis cathode, comprising the following steps:

[0034] Step 1: Mix cathode catalyst powder, anion exchange resin solution and dispersant and disperse them evenly to form cathode catalyst slurry.

[0035] Step 2: coating the cathode catalyst slurry described in step 1 on the surface of the gas diffusion layer, and obtaining the cathode gas diffusion layer after drying.

[0036] Step 3: coating the surface of the cathode gas diffusion layer in step 2 with an anion exchange resin solution to obtain an anion exchange resin coating.

[0037] Step 4: Soak the cathode gas diffusion layer having an anion exchange membrane resin coating on the surface in step 3 in an organic solvent, and use deionized water to rinse the excess organic solvent on the surface to obtain the highly active and highly stable AEM water electrolysis cathode.

[0038] In step 1, the total mass ratio of the cathode catalyst, the anion exchange resin solution and the dispersant is 1:1.1-10.8:4.5-20.

[0039] The dispersant includes a mixture of one or more of deionized water, isopropyl alcohol, ethanol and ethylene glycol.

[0040] The mixed solution is uniformly mixed by one or more of stirring, cell crushing and ice-water bath ultrasonic dispersion.

[0041] The coating method includes one or more of coating, transfer and ultrasonic spraying.

[0042] The anion exchange resin solution is coated on the surface of the cathode catalyst layer to form an anion exchange resin coating with a coating thickness of 5 to 20 um.

[0043] The organic solvent includes one or more of ethanol, isopropanol, acetone and dimethyl sulfoxide.

[0044] The volume ratio of the organic solvent to the deionized water is 1:1-25.

[0045] The organic solvent immersion time is 10 to 180 seconds.

[0046] The invention provides the application of an AEM water electrolysis cathode in a water electrolysis hydrogen separation reaction in an anion exchange membrane electrolyzer.

[0047] Example 1

[0048] Step 1: Take 10 mg of cathode catalyst powder, 11 mg of anion exchange resin solution, and 50 mg of deionized water, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes. The obtained cathode catalyst slurry has low viscosity and strong fluidity;

[0049] Step 2: Set the area to 5cm 2 The gas diffusion layer was placed on a ceramic heating plate and heated to 80°C. The cathode catalyst slurry was evenly sprayed on the gas diffusion layer at a discharge rate of 10uL / s using an ultrasonic sprayer. Cracks appeared on the surface of the prepared cathode gas diffusion layer, and some catalysts agglomerated.

[0050] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 7um;

[0051] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0052] Using an anion exchange membrane electrolyzer, the water electrolysis performance of the AEM cathode electrode at 50°C was tested. The experimental results refer to Figure 1 As shown, the electrolytic cell performance is 2.217V@10000A / m 2 .

[0053] The use of single deionized water as the catalyst slurry dispersant results in a long waiting time during the drying process on the heating table and partial agglomeration of the catalyst; although an additional anion exchange resin coating layer is used as an enhanced ion transport channel, the water electrolysis performance is still poor.

[0054] Example 2

[0055] The difference from Example 1 is that the dispersant is ethanol.

[0056] Step 1: Take 10 mg of cathode catalyst powder, 11 mg of anion exchange resin solution, and 50 mg of ethanol, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes. The obtained cathode catalyst slurry has a low viscosity;

[0057] Step 2: Set the area to 5cm 2 The gas diffusion layer is placed on a ceramic heating plate and heated to 80°C. Then, an ultrasonic sprayer is used to evenly spray the cathode catalyst slurry onto the gas diffusion layer at a discharge rate of 10uL / s. Spherical particles appear on the surface of the prepared cathode gas diffusion layer.

[0058] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 7um;

[0059] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0060] Using an anion exchange membrane electrolyzer, the water electrolysis performance of the AEM cathode electrode at 50°C was tested. The experimental results refer to Figure 2 As shown, the electrolytic cell performance is 2.02V@10000A / m 2 .

[0061] Using a single ethanol solution as a catalyst slurry dispersant will make it difficult for the coated catalyst slurry to adhere evenly to the surface of the porous transport layer. In addition, using a single ethanol solvent in the coating process will cause the catalyst layer to evaporate too quickly during the heating and drying process, causing local drying of the catalyst layer surface, while there is still residual ethanol inside the catalyst layer, resulting in tiny spherical particles on the surface; although an additional anion exchange resin coating layer is used as an enhanced ion transport channel, the water electrolysis performance is poor.

[0062] Example 3

[0063] This is the best embodiment, and the difference from embodiment 1 and embodiment 2 is that the dispersant is a mixture of deionized water and ethanol.

[0064] Step 1: Take 10 mg of cathode catalyst powder, 11 mg of anion exchange resin solution, 5 mg of deionized water and 45 mg of ethanol, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes to obtain a uniformly dispersed cathode catalyst slurry;

[0065] Step 2: Set the area to 5cm 2 The gas diffusion layer is placed on a ceramic heating plate and heated to 80°C. Then, an ultrasonic sprayer is used to evenly spray the cathode catalyst slurry onto the gas diffusion layer at a discharge rate of 10uL / s, thereby obtaining a cathode gas diffusion layer with a uniform surface.

[0066] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 7um;

[0067] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0068] The water electrolysis performance of the AEM cathode electrode at 50°C was tested using an anion exchange membrane electrolyzer. Figure 3As shown, the electrolytic cell performance is 1.865V@10000A / m 2 .

[0069] Using a combination of deionized water and ethanol as a dispersion liquid for the catalyst slurry can form a uniform slurry, which is easy to spray and prevents the catalyst from agglomerating. To a certain extent, it can also improve the wettability of the slurry to the base material and ensure uniform coating.

[0070] Example 4

[0071] The difference from Example 3 is that the coating thickness

[0072] Step 1: Take 10 mg of cathode catalyst powder, 11 uL of anion exchange resin solution, 5 mg of deionized water and 45 mg of ethanol, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes to obtain a uniformly dispersed cathode catalyst slurry;

[0073] Step 2: Set the area to 5cm 2 The gas diffusion layer is placed on a ceramic heating plate and heated to 80°C. Then, an ultrasonic sprayer is used to evenly spray the cathode catalyst slurry onto the gas diffusion layer at a discharge rate of 10uL / s, thereby obtaining a cathode gas diffusion layer with a homogeneous surface.

[0074] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 5um;

[0075] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0076] The water electrolysis performance of the AEM cathode electrode at 50°C was tested using an anion exchange membrane electrolyzer. Figure 4 As shown, the electrolytic cell performance is 1.97V@10000A / m 2 .

[0077] When the thickness of the additionally applied anion exchange resin coating layer is thin, fewer channels are generated in combination with the organic solvent, resulting in lower ion transfer efficiency and lower mechanical strength of the catalyst layer.

[0078] Example 5

[0079] The difference from Example 3 and Example 4 is that the coating thickness

[0080] Step 1: Take 10 mg of cathode catalyst powder, 11 mg of anion exchange resin solution, 5 mg of deionized water and 45 mg of ethanol, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes to obtain a uniformly dispersed cathode catalyst slurry;

[0081] Step 2: Set the area to 5cm 2 The gas diffusion layer is placed on a ceramic heating plate and heated to 80°C. Then, an ultrasonic sprayer is used to evenly spray the cathode catalyst slurry onto the gas diffusion layer at a discharge rate of 10uL / s, thereby obtaining a cathode gas diffusion layer with a homogeneous surface.

[0082] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 20um;

[0083] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0084] The water electrolysis performance of the AEM cathode electrode at 50°C was tested using an anion exchange membrane electrolyzer. Figure 5 As shown, the electrolytic cell performance is 2.160V@10000A / m 2 .

[0085] When the thickness of the additional anion exchange resin coating is thicker, more channels can be generated by combining with the organic solvent, but the transmission distance of the catalyst layer away from the AEM membrane is longer, covering the active site of the catalyst, and the ion conduction efficiency is greatly reduced.

[0086] Comparative Example 1

[0087] The difference from Example 3, Example 4 and Example 5 is that the coating thickness

[0088] Step 1: Take 10 mg of cathode catalyst powder, 11 mg of anion exchange resin solution, 5 mg of deionized water and 45 mg of ethanol, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes to obtain a cathode catalyst slurry;

[0089] Step 2: Set the area to 5cm 2 The gas diffusion layer is placed on a ceramic heating plate and heated to 80°C. The cathode catalyst slurry is evenly sprayed on the gas diffusion layer at a discharge rate of 10uL / s using an ultrasonic sprayer to obtain a cathode gas diffusion layer;

[0090] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 4um;

[0091] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution by volume for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0092] The water electrolysis performance of the AEM cathode electrode at 50°C was tested using an anion exchange membrane electrolyzer. Figure 1 As shown, the performance reaches 2.204V@10000A / m 2 .

[0093] When the thickness of the additional anion exchange resin coating film is less than 5um, bubbles will escape faster from the catalyst coating under high electrical density conditions, causing the catalyst layer to fall off and quickly lose its activity.

[0094] Comparative Example 2

[0095] The difference from Example 3, Example 4 and Example 5 is that the coating thickness

[0096] Step 1: Take 10 mg of cathode catalyst powder, 11 mg of anion exchange resin solution, 0.5 mg of deionized water and 9.5 mg of ethanol, stir for 1 hour, and immediately ultrasonically disperse in an ice water bath for 30 minutes. The obtained cathode catalyst slurry has low viscosity and strong fluidity;

[0097] Step 2: Set the area to 5cm 2 The gas diffusion layer was placed on a ceramic heating plate and heated to 80°C. The cathode catalyst slurry was evenly sprayed on the gas diffusion layer at a discharge rate of 10uL / s using an ultrasonic sprayer. Cracks appeared on the surface of the prepared cathode gas diffusion layer, and some catalysts agglomerated.

[0098] Step 3: On the surface of the cathode gas diffusion layer, an anion exchange resin coating is evenly sprayed at a discharge rate of 1.5uL / s, and the coating thickness is 21um;

[0099] Step 4: Soak the cathode gas diffusion layer electrode with an anion exchange resin coating in a 10% ethanol / water solution for 30 seconds, take out the AEM cathode after soaking for 30 seconds, and wash it with deionized water for 3 times to finally obtain an AEM cathode electrode;

[0100] Using an anion exchange membrane electrolyzer, the water electrolysis performance of the AEM cathode electrode at 50°C was tested. The experimental results refer to Figure 7, the electrolytic cell performance is 2.240V@10000A / m 2 .

[0101] When the thickness of the additional anion exchange resin coating film is greater than 20um, the catalyst will have poor flexibility and will be prone to falling off or delamination during assembly. It will also clog the pore structure, resulting in poor mass transfer.

[0102] In the description of the present invention, it is necessary to understand that the terms "coaxial", "bottom", "one end", "top", "middle", "the other end", "upper", "one side", "top", "inside", "front", "center", "both ends" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0103] In the present invention, unless otherwise clearly stipulated and limited, the terms such as "installation", "setting", "connection", "fixation", "screwing", "pad installation" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. Unless otherwise clearly defined, ordinary technicians in this field can understand the specific meanings of the above terms in the present invention according to the specific circumstances.

[0104] The above description shows and describes the preferred embodiments of the present invention. As mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an AEM water electrolysis cathode, characterized in that: The following steps are involved: Step 1: Mix cathode catalyst powder, anion exchange resin solution and dispersant and disperse them evenly to form cathode catalyst slurry. Step 2: coating the cathode catalyst slurry described in step 1 on the surface of the gas diffusion layer, and obtaining the cathode gas diffusion layer after drying. Step 3: coating the surface of the cathode gas diffusion layer in step 2 with an anion exchange resin solution to obtain an anion exchange resin coating. Step 4: Immerse the cathode gas diffusion layer having an anion exchange membrane resin coating on the surface in step 3 in an organic solvent, and use deionized water to rinse the excess organic solvent on the surface to obtain the highly active and highly stable AEM water electrolysis cathode.

2. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: In the step 1, the total mass ratio of the cathode catalyst, the anion exchange resin solution and the dispersant is 1:1.1-10.8:4.5-20.

3. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The dispersant includes a mixture of one or more of deionized water, isopropyl alcohol, ethanol and ethylene glycol.

4. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The mixed solution is uniformly mixed by one or more of stirring, cell crushing and ice-water bath ultrasonic dispersion.

5. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The coating method includes one or more of coating, transfer and ultrasonic spraying.

6. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The anion exchange resin solution is coated on the surface of the cathode catalyst layer to form an anion exchange resin coating with a coating thickness of 5 to 20 um.

7. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The organic solvent includes one or more of ethanol, isopropanol, acetone and dimethyl sulfoxide.

8. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The volume ratio of the organic solvent to deionized water is 1:1-25.

9. The method for preparing the AEM water electrolysis cathode according to claim 1, characterized in that: The organic solvent soaking time is 10 to 180 seconds.

10. Use of the AEM water electrolysis cathode according to any one of claims 1 to 9 in a water electrolysis hydrogen separation reaction in an anion exchange membrane electrolyzer.